The Rutgers Open Access Policy: Implementation Planning for Success - Mullen, Laura Bowering; Otto, Jane Johnson (Qualitative and Quantitative Methods in Libraries, 2017)
Passing a university Open Access policy creates a sense of accomplishment.  Often, the passage of a policy and/or resolution in any university follows a time period of outreach, education, and very hard work on the part of everyone involved in that policymaking. However, an implementation team must quickly be formed, and the real work begun in order for momentum to continue and success to be realized. New groups must be created, traditional silos broken down, and work tied to deadlines in order for the policy to “go into effect” as an active part of researchers’ workflows and mindsets. At Rutgers University, an open access resolution was passed by the University Senate in October, 2012, and was codified in the official Rutgers University Policy Library in October, 2014. All of the work that the authors coordinated to get to the point of passing the policy was only the beginning of making open access a reality at Rutgers. Since the date that the policy has passed, the authors have been leading an implementation effort (using an established timeline) which includes a new web portal for scholarship, as well as developing materials and presentations for various open access policy-focused education and outreach efforts. An added challenge to the Rutgers implementation is that the policy is inclusive of graduate students. This gives Rutgers, the first and only university in the world at this point to include its graduate students (doctoral students and postdoctoral scholars) alongside faculty under its university-wide open access policy, an added opportunity and responsibility to create programs and workflows for this important group of early career researchers. The authors provide background and a case study to illustrate the implementation efforts underway as Rutgers comes closer to the official date that the policy will go into effect university-wide on Sept. 1, 2015.